REVISITING THE EFFECTS OF SOCIOCULTURAL CONTEXT AND DISCIPLINES ON THE USE OF HEDGES IN RESEARCH ARTICLES - Sanjaya, I Nyoman Suka (Universitas Pendidikan Indonesia, 2015)
This study examines whether sociocultural context and discipline substantially affect usage of hedges in research articles. The corpus for the study consists of 104 research articles from two languages (English and Indonesian) with the disciplines of applied linguistics and chemistry. The analysis reveals that there is a statistically significant effect of sociocultural context in research articles from applied linguistics only. Interaction effect between sociocultural context and discipline is also observed. However, there is no statistically significant effect of the disciplines. It seems that both factors are not the major factors influencing usage of hedges in research articles. One intrapersonal factor, namely the cultural models embraced by the individual authors in regard to hedging usage, is proposed as a significant factor which determines the degree of uncertainty of research articles.Â Â Â